Sebaran Substrat Dasar Perairan Berdasarkan Nilai Hambur Balik Hidroakustik Di Perairan Sei Enam, Kabupaten Bintan - Rohmah, Roseani Baiti; Ma'mun, Asep; Febrianto, Try (Universitas Diponegoro, 2025)
The use of hydroacoustic technology, namely single beam echosounder scientific Simrad EK15 for the measurement of bottom substrate in large area coverage and accurate data. The purpose of this study was to analyze the hydroacoustic backscatter value of bottom substrate, analyze the relationship between the size of the substrate fraction to the backscatter value and map the distribution of bottom substrate in Sei Enam waters, Bintan Regency. This research was conducted on May 29, 2024-December 2024. The results obtained substrate types with a percentage distribution of 46% gravel, 30% sandy gravel, 13% gravelly sand, and 10% slightly gravelly sand. The highest average surface backscattering strength value E1 on gravel ranged from -22.76 dB to -19.84 dB with an average value of E2 ranging from -40.53 dB to -33.34 and the lowest by slightly gravelly sand substrate ranging from -26.63 dB to -25.20 dB with an average value of E2 ranging from -42.54 dB to -29.43 dB. Based on simple linear regression analysis shows the results of a very strong relationship on the size of the diameter fraction with a roughness backscatter value of 0.900 and the size of the diameter fraction of the substrate has an 81,1% influence on the backscatter value, as well as on the size of the diameter fraction has a very strong relationship with hardness of 0.868 and the size of the diameter fraction has an influence of 75.4% on the backscatter value of hardness. In the distribution of substrates from the land direction, the dominant type of gravel substrate and the direction of open water is the type of slightly gravelly sand. Penggunaan teknologi hidroakustik yaitu single beam echosounder scientific Simrad EK15 untuk pengukuran substrat dasar perairan dalam jangkauan area luas dan data akurat. Tujuan penelitian ini adalah untuk menganalisis nilai hambur balik hidroakustik substrat dasar, menganalisis hubungan antara ukuran fraksi substrat terhadap nilai hambur balik dan memetakan sebaran substrat dasar di perairan Sei Enam, Kabupaten Bintan. Penelitian ini dilaksanakan 29 Mei 2024-Desember 2024. Hasil penelitian memperoleh tipe substrat dengan sebaran persentase 46% gravel, 30% sandy gravel, 13% gravelly sand, dan 10% slightly gravelly sand. Nilai surface backscattering strength rata-rata E1 yang tertinggi pada gravel berkisar -22,76 dB sampai -19,84 dB dengan nilai rata-rata E2 berkisar -40,53 dB sampai -33,34 dan terendah oleh substrat slightly gravelly sand berkisar -26,63 dB sampai -25,20 dB dengan nilai rata-rata E2 berkisar -42,54 dB sampai -29,43 dB. Berdasarkan analisis regresi linier sederhana menunjukkan hasil hubungan yang sangat kuat pada ukuran diameter fraksi dengan nilai hambur balik kekasaran sebesar 0,900 dan ukuran diameter fraksi substrat memiliki pengaruh 81,1% terhadap nilai hambur balik, serta pada ukuran diameter fraksi memiliki hubungan yang sangat kuat dengan kekerasan sebesar 0,868 dan ukuran diameter fraksi memiliki pengaruh 75,4% terhadap nilai hambur balik kekerasan. Pada sebaran substrat dari arah daratan dominan tipe substrat gravel dan arah perairan lepas berupa tipe slightly gravelly sand.